The fabric of peace in Africa : looking beyond the state - Crocker, Chester A.; Aall, Pamela R.; Annan, Kofi A. (Kofi Atta); Centre for International Governance Innovation (Waterloo, Ontatio : Centre for International Governance Innovation, 2017)
"Over the past two decades, Africa has seen dozens of conflicts over a variety of issues. Responding to these conflicts requires concerted action to manage the crises--the violence, the political discord, and the humanitarian consequences of prolonged fighting. But it is also necessary to rebuild communities, societies and states torn apart by the conflict, addressing the long-term social and economic impact of the conflict. To do so, it is necessary to look at institutions and groups rarely considered in formal official conflict management activities of African and partner governments--schools, universities, religious institutions, media, commercial enterprises, legal institutions, civil society groups, youth, women and migrants. These entities can potentially play an important role in building a sense of identity, fairness, shared norms, and a cohesion between state and society--all critical components of the fabric of peace and security in Africa. This book brings together leading experts from Africa, Europe and North America to examine these critical social institutions and groups and identify how they can either build or impede peaceful resolution of conflicts and commitment to common purpose. This book will open new doors of understanding for students, scholars and practitioners focused on bringing strengthening peace in Africa."--
Includes bibliographical references and index.
Issued also in electronic format.
Keywords: Peace-building -- Africa; Conflict management -- Africa; Social institutions -- Africa